2017
DOI: 10.4025/psicolestud.v22i1.34674
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento Das Estratégias Inclusivas Para Estudantes Com Deficiência Intelectual E Autismo

Abstract: RESUMO.Compreender a forma como tem ocorrido a implementação das normas sobre a inclusão escolar de estudantes com deficiência intelectual (DI) e transtorno do espectro autista (TEA) pode auxiliar na caracterização de estratégias bem sucedidas, que possam servir como modelos para outras escolas, educadores ou famílias. O objetivo do estudo foi mapear as estratégias de inclusão escolar, utilizadas com dez estudantes (05 com DI e 05 com TEA), a partir da caracterização desses participantes, dos relatos de seus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 14 publications
0
5
0
17
Order By: Relevance
“…As highlighted by Gomes, Carvalho and Souza (2014), the variability in the profile of people with autism, due to the heterogeneity of the manifestation and the degree of affection of the symptoms, can be a difficulty in the planning of strategies to teach reading skills to population. Benitez, Gomes, Bondioli and Domeniconi (2017) indicated that characteristics such as age, drug treatment, intellectual quotient, receptive vocabulary of students with ASD and intellectual disability are important. However, the authors emphasize that this information can be considered generalist, that is, it does not identify basic skills, especially of academic repertoires, to direct the elaboration of teaching planning by the teacher.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted by Gomes, Carvalho and Souza (2014), the variability in the profile of people with autism, due to the heterogeneity of the manifestation and the degree of affection of the symptoms, can be a difficulty in the planning of strategies to teach reading skills to population. Benitez, Gomes, Bondioli and Domeniconi (2017) indicated that characteristics such as age, drug treatment, intellectual quotient, receptive vocabulary of students with ASD and intellectual disability are important. However, the authors emphasize that this information can be considered generalist, that is, it does not identify basic skills, especially of academic repertoires, to direct the elaboration of teaching planning by the teacher.…”
Section: Discussionmentioning
confidence: 99%
“…The target audience for special education defined in the National Policy on Special Education from the perspective of Inclusive Education (Ministry of Education, 2008) involves students with disabilities, global developmental disorders and high skills/giftedness. Regarding this audience, those who present some cognitive condition, such as intellectual disability (ID) and, in some cases, global (or pervasive) developmental disorders (PDD), seem to have need of greater educational support throughout the inclusion process in the regular classroom, mainly with relation to curricular flexibilization and performance of a collaborative special education teacher together with the general education teacher (Benitez & Domeniconi, 2018;Benitez, Gomes, Bondioli, & Domeniconi, 2017).…”
Section: Articlementioning
confidence: 99%
“…A implementação de práticas educativas inclusivas baseadas em evidências é especialmente importante na Educação Infantil, pois, nesse estágio, a criança precisa ter oportunidade de desenvolver habilidades pré-acadêmicas fundamentais para o sucesso na escolarização posterior. Como verificaram Benitez et al (2017), fragilidades no planejamento de ensino especializado para estudantes com deficiência na Educação Infantil criam grande defasagem de repertórios acadêmicos no Ensino Fundamental.…”
Section: Introductionunclassified